STATUS KERENTANAN Aedes aegypti TERHADAP INSEKTISIDA GOLONGAN ORGANOFOSFAT DAN PIRETROID DI INDONESIA - Jusniar Ariati; Dian Perwitasari; Rina Marina; Shinta Shinta; Doni Lasut; Roy Nusa; anwar musadad (JURNAL EKOLOGI KESEHATAN, 2018)
ABSTRACT The long-term use of insecticides causes resistance to targeted insects, so that a study of its resistance in Indonesia is needed. A cross-sectional study was conducted to determine the resistance status of Aedes aegypti to organophosphates and pyrethroids in 102 districts in 2015 with reference to WHO standard bioassay test. Sampling and testing of Ae. Aegypti larvae from 100 houses were carried out from three area of each health center. Test results on 0.8% malathion revealed that 84% districts were resistant, 13% districts were tolerant, and 3% districts were vulnerable. The test results for temephos of 0.02% also found that 49% districts were resistant, 29% districts were tolerant and 22% districts were vulnerable. While for 0.05% cypermethrin insecticide test; 98% were resistant, and 1% was tolerant. The test on 0.025% alpha cypermethrin found that 40% were resistant, 51% were tolerant and 9% were vulnerable. Test on 0.025% deltamethrin found that 65% were resistant, 22% districts were tolerant and 14% districts were vulnerable. With the high resistance to organophosphate and pyrethroid groups, it is recommended to rearrange the application of insecticide types in each region cyclically. Keywords: Insecticides, resistance, organophosphates, pyrethroid, Aedes aegypti ABSTRAK Penggunaan insektisida dalam jangka waktu lama menyebabkan resistensi terhadap serangga sasaran, sehingga diperlukan uji status kerentanan Ae.aegypti di Indonesia. Jenis penelitian adalah deskriptif dengan desain potong lintang. Pengambilan sampel uji (jentik Ae. aegypti) dilakukan di 102 Kabupaten/kota di Indonesia pada 100 rumah di setiap tiga wilayah kerja puskesmas. Metode uji kerentanan menggunakan bioassay test standar WHO. Hasil uji terhadap malathion 0,8% mendapatkan 86 (84%) kabupaten telah resisten, 13 kabupaten (13%) toleran dan 3 (3%) kabupaten rentan. Hasil uji terhadap temephos 0,02% menunjukkan 50 (49%) kabupaten resisten, 30 (29%) kabupaten toleran dan 22 (22%) kabupaten rentan. Hasil uji insektisida sipermetrin 0,05%, sebanyak 100 (98%) kabupaten resisten, dan 1 (1%) kabupaten toleran. Hasil uji terhadap alfa sipermetrin 0,025%, sebanyak 18 kabupaten (40%) resisten, 23 (51%) kabupaten toleran dan 4 (9%) kabupaten berstatus rentan. Hasil uji terhadap deltametrin 0,025% sebanyak 66 (65%) kabupaten resisten, 22 (22%) kabupaten toleran dan 14 (14%) kabupaten rentan. Dapat disimpulkan bahwa telah terjadi resistensi terhadap insektisida golongan organofosfat dan piretroid. Disarankan untuk mengganti kedua jenis insektisida tersebut di setiap wilayah yang teridentifikasi resitensi tinggi. Kata kunci: Insektisida, resitensi, organofosfat, piretroid, aedes aegypti